2019
DOI: 10.1063/1.5109956
|View full text |Cite
|
Sign up to set email alerts
|

Large area deep ultraviolet light of Al0.47Ga0.53N/Al0.56Ga0.44N multi quantum well with carbon nanotube electron beam pumping

Abstract: Large area deep ultraviolet (DUV) light is generated by carbon nanotube (CNT) cold cathode electron beam (C-beam) irradiation on Al0.47Ga0.53N/Al0.56Ga0.44N multi quantum wells (MQWs) anode. We developed areal electron beam (EB) with CNT cold cathode emitters. The CNT emitters on silicon wafer were deposited with an area of 188 mm2, and these were vertically aligned and had conical structures. We optimized the C-beam irradiation conditions to effectively excite AlGaN MQWs. When AlGaN MQWs were excited using an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Several groups are developing e-beam-pumped UVC emitters with various types of active regions, including powdered p-BN, [130] ZnO, [131] bulk AlGaN:Si layers, [132] and AlGaN-based MQW structures. [75,76,128,129,[133][134][135] For the latter types of the devices, the emission at 246 nm with a maximum pulse output power above 200 mW was demonstrated by Taba-Taba et al [129] under the e-beam excitation with a current of 4.4 mA and energy of 12 keV. A detailed state of the art for these emitters can be found in the review by Li et al [21] In 2018, we proposed using for e-beam-pumped UVC emitters the binary ML GaN/AlN MQW structures grown by SDA, as described in Section 2.1.4.…”
Section: High-power E-beam-pumped Uvc Emittersmentioning
confidence: 99%
“…Several groups are developing e-beam-pumped UVC emitters with various types of active regions, including powdered p-BN, [130] ZnO, [131] bulk AlGaN:Si layers, [132] and AlGaN-based MQW structures. [75,76,128,129,[133][134][135] For the latter types of the devices, the emission at 246 nm with a maximum pulse output power above 200 mW was demonstrated by Taba-Taba et al [129] under the e-beam excitation with a current of 4.4 mA and energy of 12 keV. A detailed state of the art for these emitters can be found in the review by Li et al [21] In 2018, we proposed using for e-beam-pumped UVC emitters the binary ML GaN/AlN MQW structures grown by SDA, as described in Section 2.1.4.…”
Section: High-power E-beam-pumped Uvc Emittersmentioning
confidence: 99%
“…It is generally accepted that the deterioration of the p -type doping of AlGaN layers with an increasing Al content is one of the most urgent problems of UVC LEDs. Therefore, it is of great interest to develop alternative electron-beam (e-beam) pumped UVC emitters (also called UVC-light-source tubes) based on (Al,Ga)N-based heterostructures with multiple quantum wells (MQWs) without p -type doped layers [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Moreover, these UVC emitters have demonstrated a uniquely high output optical power-up to the Watt range.…”
Section: Introductionmentioning
confidence: 99%
“…We have also found that Zn 2 SiO 4 pumped with the C-beam, that is, via CNT emitters as an electron source, obtained far UVC light at wavelengths of 208, 226, and 244 nm and that CNT emitters could be used as excitation sources to generate far UVC light . Recently, we developed 278.7 nm UVC light with AlGaN MQWs and C-beam irradiation . We obtained UVC lighting with a large area of 303 mm 2 .…”
Section: Introductionmentioning
confidence: 97%
“…EB-pumped UV light sources have been researched and developed over the last 10 years. , In 2009, Watanabe et al explored EB pumping on hexagonal boron nitride powder to obtain far UVC light with a wavelength of 225 nm and a power conversion efficiency (PCE) of 0.6% . This PCE with the EB pumping technique is higher than 0.2%, which is the external quantum efficiency of UVC-LEDs at wavelengths of 226 and 227 nm. , Oto et al reported an EB pumping technique in 2010 using AlGaN MQWs with an optical output power of 100 mW and a PCE of 40% at a wavelength of 238 nm .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation